Nesting sites of sympatrically breeding weavers: "Ploceus capensis" and "P. velatus" in mountain grasslands of southern Africa - Kopij, Grzegorz (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Studies were conducted from 1998-2002 in the Moloti/Drakensberg area, Lesotho, southern Africa. A total of 155 nesting sites of the Cape Waever and 75 nesting sites of the Southern Masked Weaver were found. Almost all nesting sites of both weaver species were situated along river courses vegetated with willows, poplars and other tree species.
Keywords: Southern Masked Weaver; Cape Weaver; breeding; nest sites; competition; Lesotho